Seasonal asset allocation: Evidence from mutual fund flows - Mark J. Kamstra; Lisa A. Kramer; Maurice D. Levi; Russ Wermers (University of Cologne, Centre for Financial Research (CFR), 2013)
Over the past 30 years, mutual funds have become the dominant vehicle through which individual investors prepare for retirement via defined contribution plans. Further, money market mutual funds, which hold 2.7 trillion as of September 2013, are now a major part of the cash economy in the U.S. Accordingly, the flow of money to and from different mutual fund categories (e.g., equities vs. money funds) increasingly reflects the sentiment or risk aversion of the general population. In this study, we analyze flows between different categories of mutual funds, and find strong evidence of a seasonality in risk aversion of individual investors. Specifically, we find that aggregate investor flow data reveals an investor preference for U.S. money market and government bond mutual funds in the autumn, and equity funds in the spring, controlling for the influence of seasonality in past performance, advertising, liquidity needs, and capital gains overhang on fund flows. This movement of large amounts of money between fund categories is correlated with a proxy for variation in investor risk aversion across the seasons, consistent with investors' revealed preferences for safer investments in the fall, and riskier investments in the spring. We find similar evidence in Canadian mutual fund flows, and in flows among Australian funds, where the seasons are six months out of phase relative to Canada and the U.S. While prior evidence regarding the influence of seasonally changing risk aversion on financial markets relies on seasonal patterns in asset returns, we provide the first direct trade-related evidence.
Keywords: G11; 330; time-varying risk aversion; sentiment; mutual fund ow seasonality; net exchanges; net ows; risk tolerance; risk aversion